2011
DOI: 10.1016/j.neuro.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of K074 and pralidoxime on antioxidant and acetylcholinesterase response in malathion-poisoned mice

Abstract: The organophosphorus (OP) pesticide malathion is a highly neurotoxic compound and its toxicity is primarily caused by the inhibition of acetylcholinesterase (AChE), leading to cholinergic syndrome. Although oximes have been used as potential antidotal treatments in malathion poisoning because of their potential capability to reactivate the inhibited enzyme, the clinical experience with the clinically available oximes (e.g. pralidoxime) is disappointing and their routine use has been questioned. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Such hypotheses are supported by our present study, since 2-PAM, known to revert DFP-induced inhibition of AChE (dos Santos et al, 2011), was neuroprotective, even in the presence of the B1BKR agonist desArg 9 -BK, which abolished protection mediated by BK. The failure of BK inducing neuroprotective pathways in the presence of desArg 9 -BK suggests that B2BKR-mediated PS recovery which is not directly connected with AChE inhibition by DFP.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Such hypotheses are supported by our present study, since 2-PAM, known to revert DFP-induced inhibition of AChE (dos Santos et al, 2011), was neuroprotective, even in the presence of the B1BKR agonist desArg 9 -BK, which abolished protection mediated by BK. The failure of BK inducing neuroprotective pathways in the presence of desArg 9 -BK suggests that B2BKR-mediated PS recovery which is not directly connected with AChE inhibition by DFP.…”
Section: Discussionsupporting
confidence: 85%
“…Pralidoxime (2-PAM), known to revert inhibition of acetylcholine esterase (dos Santos et al 2011) protected against neurotoxic effects of DFP that were not affected by the B1BKR agonist Lys-des-Arg9-BK (Figure 6). However, 2-PAM-induced PS recovery was reduced in the presence of BK and the B1BKR agonist, suggesting interference between B2BKR- and B1BKR-mediated signaling as reported previously (Martins et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ROS inhibits AChE activity. This effect was found in brain and in peripheral cholinergic nerves [31,32]. The neural system is protected by antioxidants against ROS.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the adverse effects of chronic ethanol exposure on cholinergic function in skeletal muscle are likely mediated by inhibition of AChE rather than ChAT. Since AChE is inhibited by oxidative stress [46,47,48,49], we postulate that ethanol-mediated impairment of insulin/IGF signaling and mitochondrial function, together with increased lipid peroxidation (HNE) promote chronic oxidative stress, which leads to inhibition of AChE expression in skeletal muscle. Previous studies demonstrated that inhibition of AChE is sufficient to cause myofiber atrophy and degeneration [50].…”
Section: Discussionmentioning
confidence: 99%